The ciceronian tradition of ius naturae in the diffusion of the bonum : the lecture of Philip The Chancellor - Corso de Estrada, Laura E. (2018)
Fil: Corso de Estrada, Laura E. Pontificia Universidad Católica Argentina. Facultad de Filosofía y Letras; Argentina